A passage in time. (3rd June 2014) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> There is no denying that English is an international language, and as such we must expect to encounter a multitude of local varieties: not only the national Englishes, such as American, British, Australian, etc. but also an even greater number of learner Englishes, such as French English, Brazilian English, Japanese English and the like. But the analogy between these two types of varieties must not be forced; while it would be absurd to condemn American English 'faucet' or 'Do you have children?' as errors, the same should not be said for Spanish 'a real (royal) prince' or German English 'We smoke not here'.